Bed for bedridden patient / Nurhafiz Firdaus Razali, Mohd Faiz Izuddin Azaha and Muhamad Zahrul Affendy Rasid - Razali, Nurhafiz firdaus; Azaha, Mohd faiz izuddin; Rasid, Muhamad Zahrul Affendy (Faculty of Electrical Engineering, 2014)
Bedridden bed is one project to help the disable person especially the bedridden patient. This innovation is upgrade due to its functionality, safety and comfortable that will make our life more easily especially to disabled people. The bedridden patient always feels uncomfortable when sitting on the static beds. The bedridden patient can move to another place with easier. The bedridden patient does not need the person that can move the bed. This innovation can make the bedridden patient in a high quality life. The bedridden bed has three button switches such as switch forward, reverse, and break. The bedridden bed can easily control to move forward or reverse. For safety, this bedridden also has its break. The DC motor can control to move forward, reverse, or break. The circuit uses one PIC16F877A as controller for the whole circuit. The circuit also uses the transistors and relays to acts output of the circuit. The transistors used to amplify and as switch electronic signals. It is composed of semiconductor material with at least three terminals for connection to an external circuit. A voltage or current applied to one pair of the transistor's terminals changes the current through another pair of terminals because the controlled (output) power can be higher than the controlling (input) power, a transistor can amplify a signal. The relays are used where it is necessary to control a circuit by a low-power signal because the relay can offer complete electrical isolation between control and controlled circuits. The bedridden bed use 12V DC wiper motor to the bedridden patient to move. The 12Vdc supply voltage is used to running the DC wiper motor.